THE CORRELATION THE ROLE OF SUPERVISOR TAKING MEDICINE WITH THE SUCCESS OF TREATMENT OF LUNG TB IN PUBLIC HEALTH CENTER GERAK MAKMUR SAMPOLAWA, SOUTH BUTON - Taswin Taswin; Izan - Izan; Wahyuddin - Wahyuddin; Dahmar Dahmar (Dian Nuswantoro Semarang, 2021)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterum Tuberculosis which can spread through droplets that have been infected with TB bacilli. In 2018, there was increasing case of lung TB about 33 people (4 people is broken up treatmment and failed, 29 is healed). The purpose of this study was to determine the relationship between the assistance of taking medication with the success of the treatment of pulmonary TB patients and the relationship of mentoring for repeat treatment at the puskesmas with the success of the treatment of pulmonary TB patients at Gerak Makmur Puskesmas, Sampolawa Subdistrict, South Buton District. This type of research is quantitative research using cross sectional design. The number of samples in this study were 33 people. Sampling in this study uses total sampling, which is the sample taken entirely from the population who finished treatment at the prosperous Gerak Community Health Center. Data analysis performed was univariate and bivariate analysis with chi square test. The results showed that there was a relationship between the role of the supervisor of taking drugs with the success of pulmonary TB treatment in the working area of Gerak Makmur Selatan Buton South Puskesmas with a value (p = 0,000<0,05) and there is a relationship between medical assistance and the success of pulmonary TB treatment in the working area of Gerak Makmur Selatan Buton Puskesmas with a value (p = 0.008<0,05). shows that there is a relationship between the role of the supervisor of taking drugs with the success of pulmonary TB treatment and there is a relationship between the assistance of taking drugs with the success of pulmonary TB treatment, and there is a relationship between mentoring repeat treatment with the success of pulmonary TB treatment at Gerak Makmur Selatan Buton Selatan health center.Keywoard: pulmonary TB successful treatment, supervision of taking medication